The Role of Investment Risk Perception in Improving the Relationship of Gen Z Financial Literacy to Investment Decisions - Intan Puspitasari; Endah Pri Ariningsih; Esti Margiyanti Utami; Ishak (www.amertainstitute.com, 2025)
This study examines the role of investment risk perception in mediating the relationship between financial literacy and investment decisions among Generation Z in Indonesia. Financial literacy, encompassing financial knowledge, financial attitudes, and financial behavior, is widely recognized as a critical determinant of financial decision-making. However, previous research has produced inconsistent results, necessitating the inclusion of investment risk perception as a mediating variable. A quantitative research design was employed using survey data from 100 respondents selected through probability sampling. Path analysis with SPSS was applied to test the direct, indirect, and total effects between variables. The results reveal that financial attitude has a significant direct effect on investment decisions, while financial knowledge and financial behavior show no direct influence. Conversely, financial behavior significantly affects investment risk perception, which in turn positively influences investment decisions. Moreover, risk perception mediates the relationships between financial attitudes and behavior with investment decisions, but not financial knowledge. These findings highlight that Generation Z’s investment decisions are strongly shaped by attitudes and behaviors when accompanied by an adequate understanding of investment risk. The study contributes to behavioral finance by demonstrating the importance of risk perception as a bridge between financial literacy and rational investment choices, offering insights for educators, policymakers, and financial institutions in fostering better investment practices among young investors.